Propuesta de estrategias transversales y métodos de trabajo para elaborar un plan integral desde una perspectiva comunitaria - Castilleja, Loli (Cuadernos de Trabajo Social, 2006)
The following pages are part of a more extensive report commissioned by the «Servei de politiques de diversitat i ciutadania de la Diputación de Barcelona (Area de igualtat i ciutadania) to whose officials we express our thanks for their collaboration in this publication. The complete title of the report is Integral Plans and Citizenship, a Community Perspective. The complete report is a methodological proposal based on the development of strategies which place emphasis on the community itself, and, as such, on the intervening agents, whether they be these public institutions or are part of the citizenry. We understand that to put into practice such Integral Plans – which are understood to be community development processes – the proposals must contribute to the social transformation and building up of the citizenry in our neighborhoods.